Mitochondrial quality control in neurodegenerative diseases: from molecular mechanisms to natural product therapies - Chen, Boxun; Wang, Qing; Wang, Yannan; Liu, Qingzhi; Chen, Weiyue; Mao, Hong; Li, Jiamin; Liu, Qi; Zhou, Xue (Frontiers in Physiology, 2025)
BackgroundNeurodegenerative diseases, such as Alzheimer’s disease, Parkinson’s disease, etc., are a group of complex and heterogeneous disorders characterized by progressive synaptic loss and pathological protein alterations. Mitochondria are the main source of energy produced by neurons and support the high energy consumption of the nervous system. Mitochondrial quality control, involving processes like mitophagy and mitochondrial biogenesis, is crucial for mitochondrial homeostasis, and mitochondrial dysfunction is closely related to neurodegenerative diseases pathogenesis, making targeting mitochondrial quality control a potential therapeutic strategy. Natural products offer benefits such as cost-effectiveness, fewer side effects, and other positive qualities, making them suitable choices as supplements or alternatives to traditional drugs for treating neurodegenerative diseases.MethodsA thorough search was conducted on many databases including Web of Science, PubMed, EMBASE, and MEDLINE to investigate the role of mitochondria in neurodegenerative diseases and the therapeutic effects of natural products.ResultsBy searching the relevant studies on neurodegenerative diseases and mitochondria in recent years, we observed a rise in the number of studies examining the functional characteristics and biological events of mitochondrial quality control systems in neurodegenerative diseases pathogenesis and the potential for natural products regulating mitochondrial quality control to improve neurodegenerative diseases.ConclusionThis review summarizes the functional characteristics and biological events of mitochondrial quality control systems in neurodegenerative diseases pathogenesis, and comprehensively analyzes the pharmacological mechanisms by which natural products regulate mitochondrial quality control to improve neurodegenerative diseases, aiming to provide a scientific basis for further research and new clinical drug development.